Positive & Negative Roles of Innate Effector Cells in Controlling Cancer Progression - Stolk, Dorian; van der Vliet, Hans J.; de Gruijl, Tanja D.; van Kooyk, Yvette; Exley, Mark A. (Frontiers in Immunology, 2018)
Innate immune cells are active at the front line of host defense against pathogens and now appear to play a range of roles under non-infectious conditions as well, most notably in cancer. Establishing the balance of innate immune responses is critical for the “flavor” of these responses and subsequent adaptive immunity and can be either “good or bad” in controlling cancer progression. The importance of innate NK cells in tumor immune responses has already been extensively studied over the last few decades, but more recently several relatively mono- or oligo-clonal [i.e., (semi-) invariant] innate T cell subsets received substantial interest in tumor immunology including invariant natural killer T (iNKT), γδ-T and mucosal associated invariant T (MAIT) cells. These subsets produce high levels of various pro- and/or anti-inflammatory cytokines/chemokines reflecting their capacity to suppress or stimulate immune responses. Survival of patients with cancer has been linked to the frequencies and activation status of NK, iNKT, and γδ-T cells. It has become clear that NK, iNKT, γδ-T as well as MAIT cells all have physiological roles in anti-tumor responses, which emphasize their possible relevance for tumor immunotherapy. A variety of clinical trials has focused on manipulating NK, iNKT, and γδ-T cell functions as a cancer immunotherapeutic approach demonstrating their safety and potential for achieving beneficial therapeutic effects, while the exploration of MAIT cell related therapies is still in its infancy. Current issues limiting the full therapeutic potential of these innate cell subsets appear to be related to defects and suppressive properties of these subsets that, with the right stimulus, might be reversed. In general, how innate lymphocytes are activated appears to control their subsequent abilities and consequent impact on adaptive immunity. Controlling these potent regulators and mediators of the immune system should enable their protective roles to dominate and their deleterious potential (in the specific context of cancer) to be mitigated.